Pseudomyxoma peritonei: a clinical case of this poorly understood condition - Oliveira, AM (2014)
BACKGROUND: Pseudomyxoma peritonei is an uncommon condition with an estimated incidence of one to two per million (worldwide) per year. It is characterized by the peritoneal deposition of mucinous tumors, most commonly of the appendix, and occasionally from the ovary, coupled by mucinous ascites. CASE PRESENTATION: We report the case of a 76-year-old woman who presented with increased abdominal girth and dyspnea for 2 weeks. She was diagnosed as a case of pseudomyxoma peritonei. She was submitted to right oophorectomy, omentectomy, and pseudomyxoma debulking. The histology was compatible with a mucinous tumor of colorectal/appendicular origin. Chemotherapy was not administered because of her functional status. Two years and 8 months later, she refers with postprandial fullness and has moderate ascites.